A comparative evaluation of compressive strength and antimicrobial efficacy of Fuji IX and Amalgomer CR: An in vitro study - Eina Gautam; Rani Somani; Shipra Jaidka; Sharib Hussain (Elsevier, 2020)
Purpose: To evaluate and compare the compressive strength and antimicrobial efficacy of Amalgomer CR and Fuji IX. Method: 40 restorative pellets were taken for evaluating compressive strength and 40 blood agar petridishes for antimicrobial efficacy. 40 restorative pellets were fabricated from the tested materials according to manufacturer intructions. Then the pellets were subjected to compressive strength testing using Instron Universal Testing machine. Antibacterial activity of Amalgomer CR and Fuji IX was assessed using the agar diffusion test. The powder and liquid of each test material was mixed and inserted in the punched wells (6 mm × 2 mm) in agar petridishes. An empty well was taken as control to authenticate the results. The agar plates were incubated at 37 °C for 24 h for Streptococcus mutans growth and then size of the inhibition zones was measured using vernier caliper. Results: Amalgomer CR had shown significantly higher Compressive Strength but comparable antimicrobial efficay to GIC Fuji IX. Conclusion: Amalgomer CR can be recommended as a permanent restorative material based on its better compressive strength and comparable antimicrobial efficacy to GIC Fuji IX.